Garlic and peppermint essential oils elicit plant defensive responses in sweet peppers - Ricupero, Michele; Biondi, Antonio; Campolo, Orlando; Alonso-Valiente, Miquel; Gallego, Carolina; Zappala, Lucia; Urbaneja, Alberto; Pérez-Hedo, Mertixell (Schweizerbart Science Publishers, 2023)
Exploiting plant defense mechanisms is a promising tool for pest management in modern agriculture. Plant Essential Oils (EOs) are used for the sustainable control of agricultural pests; however, their impact on plant defense has been scarcely investigated. In this work, we study for the first time whether the spraying of EOs can activate plant defense mechanisms in sweet pepper. The olfactory capacity of Encarsia formosa (Hymenoptera: Aphelinidae) to respond to defense-activated plants was used to select garlic and peppermint EOs among nine EOs sprayed on sweet peppers. The expression level of defense-related genes in plant tissues and the phytotoxicity were measured in response to EO foliar applications. Moreover, the olfactory responses of the herbivores, Bemisia tabaci (Hemiptera: Aleyrodidae) and Frankliniella occidentalis (Thysanoptera: Thripidae), and their natural enemies, Orius laevigatus (Hemiptera: Anthocoridae) and Nesidiocoris tenuis (Hemiptera: Miridae), to EO induced plant volatiles were also investigated. The gene expression analysis revealed activated jasmonic and salicylic acid defense signaling pathways in EO sprayed sweet pepper plants and a negligible phytotoxic effect was recorded. Choice tests revealed varying behavioral responses in selected insect models when plants were treated with garlic and peppermint EOs in different concentrations. Our results suggest that garlic and peppermint EO spray applications can enhance the defense mechanisms of sweet peppers and have a cascading bottom-up effects on the associated food chain. These initial findings provide a foundation for the future development of Integrated Pest Management strategies to protect solanaceous crops.